Polipropilen/üzüm sapı/çeltik polimer kompozitinin mekanik özelliklerinin atık cam elyaf ile geliştirilmesi - TAŞDEMİR, MÜNİR (My University, 2022)
In this experimental research; It has been studied to improve the properties of polypropylene grape stalk and paddy mixtures by adding waste glass fiber. The potential of waste grape stalk and paddy to be a reusable material has created another curious subject. Polypropylene grape stalk and paddy were mixed in a twin screw extruder to provide a homogeneous mixture. Paddy; It is known as rice husk. Grape stalk-paddy was added to the PP at the rate of 20%. Glass fiber was added at 10-15% and 20% rates. Then the test samples were molded on the injection machine. Molded samples; Tensile, hardness, impact, density and scanning electron microscopy tests were performed. By examining the results of the tests, the effects of grape stalk-paddy and glass fiber amount on polypropylene were determined.

Bu deneysel araştırmada; polipropilen (PP) üzüm sapı ve çeltik karışımlarının özelliklerinin atık cam elyaf ilavesi ile geliştirilmesi üzerine çalışılmıştır. Atık olan üzüm sapı ve çeltiğin yeniden kullanılabilir bir malzeme olma potansiyeli diğer merak edilen bir konuyu oluşturmuştur. Polipropilen üzüm sapı ve çeltik çift vidalı ekstrüderde homojen bir karışım sağlamak için karıştırılmıştır. Çeltik; pirinç kabuğu olarak bilinmektedir. PP içerisine %20 oranında üzüm sapı-çeltik katılmıştır. Cam elyaf ise %10-15 ve 20 oranlarında katılmıştır. Daha sonra enjeksiyon makinesinde test numuneleri basılmıştır. Kalıplanan numunelere; çekme, sertlik, darbe, yoğunluk ve taramalı elektron mikroskobisi testleri yapılmıştır. Testlerin sonuçları incelenerek üzüm sapı-çeltik ve cam elyaf miktarının polipropilen üzerindeki etkileri belirlenmiştir.
Improving the mechanical properties of polypropylene/grape stalk/paddy polymer composite with waste glass fiber
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Polimerik Malzemeler; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Polymeric Materials; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING; Polipropilen; üzüm sapı; çeltik; mekanik özellikler; polimer kompozit; Polypropylene; grape stem; rice husk; mechanical properties; polymer composite